Pertanggungjawaban Mutlak Korporasi sebab Kebakaran Lahan Mengakibatkan Pencemaran/Kerusakan Lingkungan HidupPertanggungjawaban Mutlak Korporasi sebab Kebakaran Lahan Mengakibatkan Pencemaran/Kerusakan Lingkungan Hidup - Naldo, Rony Andre Christian; Purba, Mesdiana (Jurnal Ilmiah Penegakan Hukum, 2018)
Absolute Accountability Corporations because Land Fire Causes Pollution / Environmental Damage. As a legal subject, in carrying out business activities, each corporation is obliged to maintain the sustainability of environmental functions, by preventing pollution / damage from exceeding the quality standards / standard criteria for environmental damage. In fact, there are various corporations whose land is burned, resulting in pollution / damage exceeding the quality standards / standard criteria for environmental damage. This study discusses the absolute responsibility of corporations because land fires result in pollution / damage exceeding the quality standards / standard criteria for environmental damage. In connection with this, this study discusses further about the application, constraints, and solutions to the application of absolute responsibility to corporations because land fires result in pollution / damage exceeding the quality standards / standard criteria for environmental damage. This study uses a type of normative legal research, with a holistic normative juridical method, and is descriptive analytical. The results of the study concluded that not all Judges of the public justice institutions applied absolute responsibility to corporations because land fires resulted in pollution / damage exceeding the quality standards / standard criteria for environmental damage. There are 4 (four) constraints and 7 (seven) solutions to the application of absolute responsibility to corporations because land fires result in pollution / damage exceeding the quality standards / standard criteria for environmental damage.